Valores de referência e reprodutibilidade do teste de exercício cardiopulmonar em crianças e adolescentes saudáveis - Selman, Jessyca Pachi Rodrigues (2020)
The cardiopulmonary exercise test (CPET) is the gold standard in the assessment of physical activity. However, normative values and to know the variability of measures in this test are crucial for proper interpretation. Objective: Study 1: To establish reference values for the CPET (cycle ergometer) in children and adolecents (aged from 6 to 18 years). Study 2: To test the reproducibility of CEPT in individuals under 18 years of age. Method: Cross-sectional study. For Study I, 260 individuals (6 to 18 years, 11 months and 29 days) were submitted to bioimpedance, spirometry, evaluation of leg length and thigh circumference, answerers of questions and performed or CEPT (CEPT -1). For Study II, 130 volunteers was maked an additional visit (72 hours apart), to perform the second CEPT (CEPT -2). Results: Study I - The following reference equations were established: Total sample: predicted VO2, L/min = -1,679 (0.025 x leg length, cm) + (0.023 x thigh circumference, cm) (R2 = 0.497) and predicted load, watts: -236.983 + (191.823 x height, m) + (34.879 x sex, 0 for girls and 1 for boys) + (3.289 x age, years) (R2= 0.751); children: PREDICTED VO2, L/min = -3.259 + (0.027 x leg length, cm) + (0.060 x thigh circumference, cm) + (1.271 x height, m) (R2= 0.477) and predicted load, watts: -125.840 + (142.437 x height, m) (R2= 0.471) and adolescents: PREDICTED VO2, L/min = -0.725 + (0.023 X leg length, cm) + (0.022 x thigh circumference, cm) + (-0.051 x age, years) (R2= 0.547) and Predicted workload, watts: -339.638 + (224.416 x height, m) + (50.467 x sex, 0 for girls and 1 for boys) + (6.077 x age, years) (R2= 0.706). Study II – Seventy percent of the sample performed better in CEPT -1. VO2peak was different in the total sample and in the group of adolescents (p =0.010), with mean differences of 0.26 L/min and a wide 95% confidence interval (-0.26 to 1.96 L/min). Conclusion: We established prediction equations for VO2 and peak workload for the CPET (cycle ergometer) in Brazilian children and adolescents. The tests were reproducible and we suggest that only one CPET is enough to assess exercise capacity in Brazilian individuals aged 6 to 18 years.